Factors Associated With Short- and Long-term Liver Graft Survival in the United Kingdom: Development of a UK Donor Liver Index. Issue 4 (April 2017) - Collett, David; Friend, Peter J.; Watson, Christopher J. E.
Abstract : Background: A measure of donor liver quality, the donor liver index, was developed and validated for the UK population of transplant recipients. Unlike previously proposed measures, this index is only based on variables that are available at the point of retrieval, and so does not include cold ischemic time. Methods: Indices of liver quality were based on data from the UK Transplant Registry on all 7929 liver transplants between January 2000 and December 2014. Results: The donor liver index (DLI) was based on factors shown to affect graft survival, which included donor age, sex, height, type (donor after brain death or circulatory death), bilirubin, smoking history, and whether the liver was split. A separate index (DLI1) looking at 1-year survival showed donor cardiac disease, black ethnicity, and steatosis to be additional risk factors. A strong association was found between DLI and whether or not a surgeon accepts an offered liver for transplant, with a marked fall in acceptance rates for livers with an index greater than 1.31. Since 2000, there has been a notable reduction in the quality of livers transplanted, coupled with variation between the 7 UK liver transplant centers in risk appetite. Conclusions: The DLI is an index of liver quality which enables analysis of the changing trends in liver quality and center behavior. DLI1 enables identification of factors affecting shorter-term survival, and perhaps identifies a cohort of livers that may benefit from novel preservation technologies. Abstract : Using data from the UK Transplant Registry, the authors develop a UK index of liver "quality" called the UK Donor Liver Index, which relates to the point of retrieval without reference to ischemic times, and estimates the risk of graft failure based on donor factors. Supplemental digital content is available in the text.